Identification of Subsurface Structures of Geothermal Potential Area in East of Mount Lawu Using The Gravity Method - Sorja Koesuma; Mela Budiani Septianingsih; Budi Legowo (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2020)
Information about the eastern side subsurface stones of Mount Lawu regarding geothermal potential is limited. This research was conducted to provide information regarding geothermal potential in those area by using the gravity method. We did a 18 sites of gravity surveys in eastern flank of Mount Lawu where located in Magetan regency, Ngawi regency and Sragen regency, East Java. The principle of this method is to measure the earth's gravity field, then the value of gravity is corrected by some gravity corrections, i.e. height, tide, drift, normal gravity, free-air, Bouguer and terrain corrections. The Complete Bouguer Anomaly (CBA) shows the formation that related to the rock formation in the subsurface of Mount Lawu. Based on CBA modelling we found that in the eastern flank of Mount Lawu contains of tuff and breccia of volcanic rocks, breccia Jabolarangan and tuff Jabolarangan, lava andesite, igneous rock (pumice), and sedimentary rocks in the form of sandstone and clay. We found a fault structure on six tracks of a research area. Otherwise, we estimated that there is a geothermal potential on the southeast side of the research area